Design and Implementation of Computer Numerical Controlled Milling Machine for Printed Circuit Board Fabrication - Zakaria Abdulftah Aldeeb; Abdulhamed Mohamed Hwas (African Journal of Advanced Pure and Applied Sciences, 2025)
For several years, printed circuit board fabrication manufacturing has been using acid etching to build electronic boards. However, the evolution of technology required more delicate and precise board schematic diagrams, at the same time Computer Numerical Control (CNC) machines were also improving over the years and proved their accuracy and preciseness. Therefore, the combination of the CNC machine and milling head can achieve precise engraving for the printed circuit board diagram with promising results. This project introduces the basic steps to building a CNC milling machine for a printed circuit board. Building a CNC machine requires a combination of mechanical, electrical, and computer-controlled systems. In this project, a frame of the machine is designed using aluminum and 3D printed parts, and stress analysis for the machine frame is proposed. Mechanical motors, bearings, and other parts are selected to meet the machine's requirements. Open-source software programs are used to operate the machine based on the computer-designed diagram model. Then, milling was performed on the single-sided copper-clad sheet to construct an electronic circuit to evaluate the machine's performance. Test results confirmed that the machine operated smoothly and consistently as required.